The Renaissance conscience - Braun, Harald (Harald Ernst); Vallance, Edward, 1975- (Malden, MA : Wiley-Blackwell, 2011)
"The Renaissance Conscience presents one of the first modern studies to explore the variety of ways in which people during the Renaissance conversed with - and let themselves be guided by - their conscience. Through the careful examination of a wide range of extant sources including theological manuals, legal treatises, letters, and literary and autobiographical texts, the authors illustrate how individuals in England and the Hispanic world during the period of the Renaissance sought to reconcile their private and public selves, and thus establish and protect their identity. Individual essays demonstrate the significance, diversity, and fluidity of notions of conscience in the early modern world. These thought-provoking case studies also reveal how authority figures and commoners from two distinct cultural spheres struggled with similar issues and did so with explicit reference to shared scholastic and humanist traditions - often with similar outcomes. The Renaissance Conscience sheds important new light on the ways in which medieval and Renaissance discourses on conscience impacted upon early modern life and anticipated contemporary notions of moral autonomy"--
Front Matter -- Introduction / Harald E Braun, Edward Vallance -- Jean Gerson, Moral Certainty and the Renaissance of Ancient Scepticism / Rudolf Schussler -- Conscience and the Law in Thomas more / Brian Cummings -- Guided by God beyond the Chilean Frontier: The Travelling Early Modern European Conscience / Andrew Redden -- Shakespeare's Open Consciences / Christopher Tilmouth -- Women's Letters, Literature and Conscience in Sixteenth-Century England / James Daybell -- The Dangers of Prudence: Salus Populi Suprema Lex, Robert Sanderson, and the Case of the Liturgy / Edward Vallance -- El governador christiano / Harald E Braun -- Spin Doctor of Conscience? the Royal Confessor and the Christian Prince / Nicole Reinhardt -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Conscience -- England -- History; Conscience -- Spain -- History; Conscience -- Latin America -- History; Renaissance -- England; Renaissance -- Spain; Renaissance -- Latin America; Civilization, Modern -- Moral and ethical aspects; Philosophy; PHILOSOPHY -- Ethics & Moral Philosophy; Civilization, Modern -- Moral and ethical aspects; Conscience; Renaissance; Etik -- renässansen.; England; Latin America; Spain; Electronic books; History